Sarafal Anam Sebagai Media Edukasi Budaya: Meningkatkan Kesadaran Generasi Muda Terhadap Warisan Leluhur - Putri, Wina Sagita; Santi, Fitria Lala; Salsabila, Suci; Aprilianti, Maya; Fadhilah, Anita; Julir, Nenan (PPSDP Undergraduate Journal of Educational Sciences, 2024)
The research aims to make the younger generation aware of the importance of preserving their ancestral cultural heritage. The method used in this research uses qualitative research methods with a descriptive approach. The results of this research show that the young generation of Tengah Padang village, Talang Empat District, Central Bengkulu Regency is aware of the importance of inheriting the original culture of their ancestors. This is influenced by the important role of the previous generation in continuing their task of introducing and teaching the younger generation about the original ancestral culture (Sarafal Anam).